Anthropometric variability, equipment usability and musculoskeletal pain in a group of nurses in the Western Cape - Botha, Winifred Edna (Department of Human Biology, 2017)
This study examined the anthropometry and anthropometric fit of a group of ward and theatre nurses in Western Cape private hospitals. Anthropometric variables were measured using a sample of nurses and a correlation matrix generated. All nurses were given a questionnaire concerned with operational problems in the work environment and musculoskeletal pain. The questionnaire was also completed by a group of sedentary nurses. The ward and theatre nurses reported numerous problems in the working environment, including lumbar backache, inadequate space and equipment that caused bodily discomfort. There were consistent, statistically significant associations between the frequency of occurrence of these problems and the anthropometric data indicating that the problems were caused or amplified by body size variability and were not simply general usability problems which would affect all nurses irrespective of their body dimensions. Further studies testing specifically for the consequences of mismatches and body size variability are recommended.